2018
DOI: 10.3390/su10061963
|View full text |Cite
|
Sign up to set email alerts
|

Indicators of Land Insecurity for Urban Farms: Institutional Affiliation, Investment, and Location

Abstract: Abstract:As urban agriculture (UA) continues to expand in the United States, many practitioners question its continuation in cities with high property values and increased economic incentives for development. Frequently, these pressures make urban farmers anxious about investing resources, time, and energy in land suitable for food production if tenure is insecure. Despite these concerns, UA continues to persist in areas experiencing increased property values and rent-seeking. Based on surveys with over 56 urb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…However, the ways in which social innovations materialise are not exclusively positive, thus, it is important to heed to the unintended consequences of such projects (Sveiby, Gripenberg, and Segercrantz 2012). For example, this could include urban community gardens contributing to an increase in property values and gentrification, potentially reinforcing inequalities they intended to counteract (Arnold and Rogé 2018;Checker 2011;Voicu and Been 2008).…”
Section: Discussionmentioning
confidence: 99%
“…However, the ways in which social innovations materialise are not exclusively positive, thus, it is important to heed to the unintended consequences of such projects (Sveiby, Gripenberg, and Segercrantz 2012). For example, this could include urban community gardens contributing to an increase in property values and gentrification, potentially reinforcing inequalities they intended to counteract (Arnold and Rogé 2018;Checker 2011;Voicu and Been 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Land security is the most frequently recorded challenge that can directly influence the long-term sustainability of urban agriculture, which has been proven by many previous studies [87][88][89]. Land insecurity can incentivize rent-seeking behavior, and therefore, urban agriculture is at risk of highest and best use developments [90].…”
Section: Contribution Of Studies On Urban Agriculturementioning
confidence: 97%
“…The reviewed articles depict this support as mainly including support given by municipal councils or local governments and policies to integrate agriculture into urban planning. High financial and institutional support can make urban agriculture activities more secure in cities [87]. However, the attention on government initiatives in academic literature is limited and significantly less in developing countries.…”
Section: Contribution Of Studies On Urban Agriculturementioning
confidence: 99%
“…Land tenure insecurity directly contributes to lack of access as many urban farms formerly serving minority and immigrant populations have been forcibly closed due to development priorities for privately owned lots (i.e., La Finquita in Philadelphia, PA; South Central Farm serving predominantly Latino households in L.A.; Free Farm in San Francisco; Brooklyn Community Farm in NYC). A recent article on land security indicators among California urban farmers showed that farms with higher land security also had "more financial and institutional support, and are located in census tracts with higher economic opportunity" [71]. This highlights the necessity of devoting publicly owned lands to urban agriculture in low income and minority neighborhoods, as private lands are highly vulnerable to development pressures, thus jeopardizing any gains realized by social justice oriented urban farms (explored further in Section 5.2 below).…”
Section: Cost Of Land and Labormentioning
confidence: 99%
“…Strategic public land grants (or land provided by land trusts) have potential to redress historic exclusions of minority farmers from land access, resources, legal expertise, and opportunities for wealth accumulation. By publicly confronting land insecurity and tenure arrangements, policymakers can directly respond to research on UA's uneven development [1,25,71]. Overall, there are multifaceted criteria in creating a balanced, equitable city food system (See [127] for consideration of justice and sustainability at all scales and the mix of solutions needed for food system reform).…”
Section: City Planning Spotlight: Nycmentioning
confidence: 99%